Perceptions of Criminology and Non-Criminology Students on Management of Arms and Ammunition from Selected University in Metro Manila - Gantalao, Jilmar S. (Future Science / FSH-PH Publications, 2022)
The increasing rate of gun-related deaths in the Philippines is one of the challenging variables in the management of arms and ammunition for effective safekeeping operations. This study describes the perceptions of the students towards management or arms and ammunition, and the relationship between the profile variates of the two-groups of respondents and the level of awareness on management of arms and ammunition. This descriptive correlational research determined the perceptions of 200 students towards management or arms and ammunition, and the relationship between the profile variates of the two-groups of respondents and the level of awareness on management of arms and ammunition. A researcher-developed questionnaire was utilized. During the conduct of the study, strict ethical principles including confidentiality and non-disclosure agreement were considered. Data were analyzed using frequency, percentage distribution, mean, rank, and Pearson's correlation coefficient. Accordingly, Carrying of Firearms Outside of Residence or Place of Business has the highest mean score of 3.39, interpreted as Highly Aware, Abandoned Firearms and Ammunition, and Death or Disability of the Licensee with a mean score of 1.95, interpreted as Slightly Aware (SA). The year level , number of trainings attended , gun ownership , family monthly gross income show significant relationships to the criminology student respondents level of awareness on effective strategies in weapons and ammunition management. Further, the number of trainings attended , gun ownership , and family monthly gross income show significant relationship to the non-criminology student respondents level of awareness on management of arms and ammunition. The majority of the respondents concur that the importance of having the permit to carry firearms outside of residence or place of business issued by the Chief, PNP, or by his/her duly authorized representative to the licensed citizen allowing him/her to carry the firearm outside the residence or place of business, as such, display of firearms is prohibited. Furthermore, the year level, number of training attended, gun ownership, and family monthly gross income has a direct positive effect on the criminology student respondents level of awareness on effective strategies in weapons and ammunition management, while the number of training attended, gun ownership, and family monthly gross income has a direct positive effect on the non-criminology student respondents level of awareness on management of arms and ammunition. Therefore, school administrators should provide and recalibrate complete gun safety training to ensure those gun owners are educated on the responsible practices for handling and using firearms, storing them securely at home, as well as carrying guns in public. Further studies may be conducted on policy analysis, enforcement, and analytical methods are applied to curb firearms-related violence.